(3eUHGM GdgOGjI hefgGL GdhdGjIs - (3YdhGf, Ydj Hf YWjI Hf GdMSf, J (B936 (3g`s ((3eMeO Hf CMeO GdMeGej GdMehj GdTGaYj GdfbTHfOjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hHg GdYUeI hgh MSHfG hfYe Gdhcjd eG TGA Gddg hdG bhI GdG HGddg QHfG BJfG ef dOfc QMeI hgjF dfG ef CeQfG QTOGs
(3BNQgG (B:s
(3ceG EPG cGfJ LjaI edbGI HGdbQH ef GdeGA hMed GdQjM QGjMI Jdc GdLjaI ahVYJ aj GdeGA aJZjQ hGddg CYde hGdMeO ddg GdPj habfG hbOQfG Ydi ceGdg hfSCdg JYGdi Cf jchf NGdUG dhLggs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 312s
(3eYLe GdeDdajf (B2 / 476s
(3TPQGJ GdPgH (B8 / 217s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdTGaYjs